Sociology - Macionis, John J. (Singapore, 2007)
Sociology, the study of human behavior in social groups, is a relatively recent discipline within the social sciences, which examine human behavior, culture, and society using scientific methodology in both research and analysis. This resource explains the rise of the social sciences, in particular sociology, charting the history of the discipline and its founders. The key principles and fundamental theories are examined in detail, and the contemporary status of sociology and today's major players are noted. Readers will also learn the importance of methodology in sociology and all social sciences--Provided by the publisher
Keywords: Sociology